A REVISION OF THE GENUS CEPHALOMAPPA (EUPHORBIACEAE) IN MALESIA - RATNA WIDURI; PETER VAN WELZEN (REINWARDTIA, 1998)
The Malesian genus Ceplialomappa Baillon has been revised. Five species have been recognized based on morphological and anatomical characters, e.g. C. beccariana, C. lepidotukt, C. malloticarpa, C. paludicola, C. penangensis, and four varieties within C. beccariana.The genus Muricococcum has been reinstated,the single species M. sinense is considered to differ significantly from the species of Cephahmappa to warrant generic recognition. A phylogenetic analysis of the genus, with Koilodepas as outgroup, shows the species to branch off sequentially, the first is C. paludicola, followed by C. malloticarpa, C. lepidotula, and finally C. penangensis and C.beccariana. All varieties of C. beccariana group together as a single terminal polytomy.